2021
DOI: 10.5334/bc.94
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking retrofit of residential heritage buildings

Abstract: What are the opportunities and challenges for upscaling the energy retrofit of heritage buildings? Heritage buildings comprise approximately 20% of the UK building stock and are challenging to retrofit sensitively because of their heritage values and traditional construction. These buildings may therefore be unconducive to standard retrofitting approaches. Twelve case studies in the UK are examined. Three key findings are presented together with their implications for upscaling retrofit. First, heritage reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The case studies were chosen from amongst the survey respondents to cover a range of building types, ages, locations, and household compositions. More details on the case studies can be found in [20]. Both the survey and case studies received ethical approval.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The case studies were chosen from amongst the survey respondents to cover a range of building types, ages, locations, and household compositions. More details on the case studies can be found in [20]. Both the survey and case studies received ethical approval.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the survey respondents, almost all case study participants were content with current thermal conditions in their homes, apart from CS2 and CS10 who were both dissatisfied with their current heating systems and were actively looking to improve them. Many of the participants (CS1, CS5, CS6, CS11, CS12, CS14) who were thermally comfortable nevertheless recognised that their homes have lower than average temperatures and that visitors sometimes found conditions cold [20]. They identified that they had acclimatised to conditions in their homes, and moreover, that they engaged in practices such as wearing additional layers which meant that they found their buildings comfortable.…”
Section: Thermal Comfortmentioning
confidence: 99%
“…While using technological systems and techniques as part of the preservation process, heritage building maintenance and upgrading helps to ensure the continuity of the building, increase its lifespan, preserve its value, and achieve sustainability and interaction requirements [44]. It also helps maintain the building's fabric and all defective services.…”
Section: Historical and Heritage Buildingsmentioning
confidence: 99%
“…Some arguments against the adaptation of historical buildings said that coping with the complexity of environmental and socioeconomic factors was difficult [21]. However, considering the environmental benefits of climate adaptation, low-carbon emissions, material recycling, and intensive land use, the regeneration of built heritage Tulous is still important for sustainability [22,23]. Previous studies have analysed critical points of conservation and regeneration for built heritage Tulous, but environmental adaptation has not been clearly articulated.…”
Section: Introductionmentioning
confidence: 99%